Tadabbur analysis of the Concept of Wahdah Al-Wujud in The Quran: Analisis Tadabbur Konsep Wahdah Al-Wujud dalam Al-Qur’an - Muhammad Alfan Sidik (Institut Agama Islam Negeri Kerinci, 2022)
Wahdah al-wujud in Islamic philosophy is a fairly complex and complicated study in debate, especially among scholars of Islamic philosophy who try to connect it with Sufism. This relationship seems to be important because of the demands for rational and logical explanations in approaching religion from the spiritual and intellectual side. This paper examines the concept of Wahdah al-wujud contained in the verses of the Qur'an and tries to analyze the relevance and harmony of its meaning. This research is a literature review using the theory of Wahdah al-wujud from Ibn 'Arabi. From this discussion, it was found that several verses studied, namely Surah al-Hadid: 3, Annisa: 126, al-Baqarah: 115, al-Mujadilah: 7, and several other verses, explain that all of the verses above show the absolute unity of God in harmony. with the understanding of Wahdah al-wujud. The absolute oneness of God shows that He is present in all entities and at the same time is not limited by all entities. Tadabbur some of the verses above, give some messages as follows; awareness of the weak position of humans as creatures of Allah, awareness of the greatness of Allah and human smallness, awareness of humans wherever they are, they can always remember Allah, dhikr to Allah swt, and this closeness to God can be grateful for as a form of honor. because humans are never separated from God.